Evaluation of Protocol Biopsy Utility 12 Months after Renal Transplantation: A Multicenter Observational Analysis - Bruno Moulin; Pierre Merville; Karine Renaudin; David Buob; Sophie Ferlicot; Michel Delahousse; Jacques Dantal; Laetitia Albano; Christelle Barbet; Georges Mourad; Laure-Hélène Noel (Journal of Transplantation)
The clinical merit of surveillance kidney graft biopsies remains controversial. A retrospective, multicenter analysis evaluated 12-month surveillance biopsies (SB, 154 patients) versus no SB (NSB, 138 patients (11 with diagnostic biopsy)) in patients >18 months posttransplant with estimated GFR (eGFR) ≥30 mL/min. The primary objective was to describe renal function at 18 months post-transplant in patients with or without SB at month 12. Globally, most recipients in both cohorts were at low immunological risk (<10% of patients with PRA ≥30%). The immunosuppressive regimen remained unchanged following more than half of SB that exhibited chronic lesions (18/33, 54.5%). Mean (SD) eGFR at month 18 (primary endpoint) was 56 (19) mL/min/1.73 m² with SB and 54 (15) mL/min/1.73 m² with NSB (𝑃=0.48). In the SB group, slight nonspecific changes were observed in 51 cases, rejection (acute or chronic) in 6 cases, CNI-related toxicity in 15 cases, recurrence of initial disease in two cases, and interstitial fibrosis/tubular atrophy (IF/TA) in 83 cases (71.6%), of which 35 cases (30.2%) were grade II/III lesions. eGFR <50 mL/min/1.73 m² at month 6 predicted IF/TA grade II or III (OR 3.85, 95% CI 1.64, 9.05, 𝑃<0.002). SB at 12 months posttransplant did not prompt significant modification of immunosuppression, and no renal benefit was observed.